Assessing boro rice yield variances across varied seedling ages to address early flash flood vulnerabilities in the Haor area of Bangladesh - Islam, M S; Mazumder, M N N; Sarmin, T; Ali, M I; Hossain, M S; Chowdhury, S M A (Bangladesh Journal of Nuclear Agriculture, 2024)
Haor is one of the most flood-prone areas of Bangladesh and it underlies in water for several months of a year. Boro rice cultivation in this area is challenging due to the flash flood. An experiment was conducted to examine the suitability and productivity of four rice varieties transplanted in different seedling ages. This experiment was carried out at Sunamganj district for two consecutive years of Boro season in 2021-22 and 2022-23. Four Boro rice varieties namely Binadhan-10, Binadhan-17, Binadhan-24, BINA dhan25, and three seedling ages (i.e., 30, 35 and 40 days old seedlings) were used as treatment in the experiment. It was conducted through a split-plot design with three replications placing seedling ages in the main plot and crop varieties in the subplot. Transplanting of 30 days seedlings of Binadhan-24 produced the highest mean grain yield of 7.8 t ha-1 and 8.2 t ha-1 while 35 days seedlings produced 7.6 t ha-1 and 7.7 t ha-1 respectively, in two consecutive years, the highest among all varieties. The maturity period among crop varieties varied due to the changes in seedling age as lower seedling age showed an earlier maturity period. So, transplanting of 30-35 days seedlings can be recommended for Binadhan-24 cultivation in the haor area. Bangladesh J. Nuclear Agric, 38(1): 41-52, 2024